Optimization of resonator design for vibration-based electromagnetic energy harvester - Seong, Tony Ow Koon; Salleh, Hanim; Nordin, Anis Nurashikin (Trans Tech Publications Ltd, 2014)
This paper presents an optimization on the resonator, which is one of the main components of electromagnetic energy harvester, using static structural analysis, stress analysis and modal analysis. The electromagnetic energy harvester is a vibration-based energy harvesting technology which has emerged as a solution for powering autonomous sensor nodes to increase their life span. Electromagnetic energy harvester acts as a transducer that converts ambient vibration energy to electrical power. An initial design of the resonator is developed and analyzed using ANSYS software. Static structural analysis and stress analysis have been performed to analyze different resonator designs to produce an optimum resonator model. Maximum static deflection under gravitation force was found to be 104.12 μm. Resonance frequency of the resonator was found to be 261.56Hz by using modal analyses. The selected resonator design was further modified to cater for wide-band frequency application as well as to have better performance. Four resonators with different beam lengths were combined in a model in order to operate at a wider frequency range. Five models were generated and the smallest frequency range is from 272 Hz to 299 Hz by model 5110_5410. The maximum power and minimum power that can be generated for this model is 135 μW and 93.9 μW respectively. The model 3910_4210 which has the highest frequency range generated a maximum power of 437 μW and minimum power of 270 μW at a frequency range of 422 Hz to 466 Hz.